SER: An R package to characterize environmental regimes - Wu, Naicheng; Guo, Kun; Zou, Yi; He, Fengzhi; Riis, Tenna (Ecology and evolution, 2023)
Environmental regimes (or environmental legacy or historical legacy) are the dynamics of environmental characteristics over a given (either long or short) time period, such as frequency of mean or extreme events and rate of change, which might be absent by using only contemporary variables. We present SER, an R package for estimating environmental regimes for different environmental variables. Using the data included in the package, several examples are shown. SER is suitable for any type of environmental or biotic variables, including nutrient concentration, light, and dissolved oxygen. In addition, by changing the argument “days_bf,” it is possible to compute environmental regimes over any time period, such as days, months, or years. Our case study showed that the inclusion of environmental regimes increased the explained variation of temporal β‐diversity and its components. Environmental regimes are expected to advance the “environment–community” relationships in ecological studies. They can further be implemented in other subjects such as social science, socioeconomics, and epidemiology. We present a new R package to compute environmental regimes over a certain period, which has important implications for basic and applied ecology, as well as other subjects.